A Note on the Fictional Non-Human in Haviva Pedaya’s The Eye of the Cat - Gal, Noam (MiKAN, 2014)
Pedaya’s novel The Eye of the Cat (2008) draws parallel lines between different neglected beings from the margins of the urban space of poor neighborhoods in contemporary Be’er Sheva. Within the same expanded rubric of otherness, Pedaya represents stray cats, homeless people and women whose entire lives are dedicated to the maintenance of their pets. Despite this comparative approach, Pedaya clarifies that methodologically the novel has been written in a way that distinguishes documentary presentation of animals from fictional representation of human characters. My essay wishes to explore this authorial decision and tries to explain it and its effects. This important poetical decision, I argue, derives from the assumption that the fictional contradicts the natural – a contradiction which defines the natural in the first place. In Pedaya’s novel, there is an ethical horizon to that assumption: the author explicitly avoids the personification of animals in her text, since personification is regarded as interruption in the animal’s realness, realness that is external to the literary text. My paper will try to explain the tension between Pedaya’s poetics and her ethical manifesto by investigating and developing the literary trope of personification.